MARKET AND STATE AGAINST LIFE: MARKET AND STATE AGAINST LIFE - Aguirre Salas, Andrea (Universidade de Brasília, 2021)
This article contributes to the study of market and state dynamics combined in the precariousness of life and the reproductive capacity of the absolutely impoverished population in the context of economic globalization. For this, the case of the penalized population in the city of Quito, capital of Ecuador, between 1980 and 2020 is analyzed. This time span allows a common criticism of two apparently antagonistic state projects, the neoliberal and the progressive neo-developmentist. Keywords: reproductive work; drug policy; criminal sanction; advanced capitalism; state.